344 A Rare Case of Meckel's Diverticulitis With a 3 Cm Enterolith. (19th August 2022) - Abunaser, M; Sabri, S; O'connor, A; Arora, P; Andrews, C
Abstract: Meckel's diverticulum (MD) is a rare condition that affects only 2% of general population. Only 4 to 6% of those Meckel's diverticulea are symptomatic. Furthermore, having a MD containing enterolith is extremely rare, and herein we present a case of 55-year-old lady with Meckle's diverticulitis containing a 3 cm enterolith. The patient presented with symptoms mimic appendicitis; however, upon further evaluation with an enhanced abdomino-pelvic CT an MD containing enterolith was confirmed. An interval laparoscopically assisted diverticulectomy was performed and the patient recovery was un-eventful.